الصورة الشعرية في ديوان "ردة نعل" لمحمود عياشي - مردف، سعد; غريبي، الطاهر; براهمي، عمر; زواري، أحمد فوزي (University of Eloued جامعة الوادي, 2024)
"Rose sandal"By the poet Mahmoud Ayashi, and it is worth noting that the poet’s poetic discourse is charged with poetic images of various types, styles, and connotations, and this is what gave the collection creative power.HajjaayasThe aesthetic is clearly visible, and the poet has succeeded in employing poetic images to serve his purposes and themes.
811/ 027
Keywords: Diwan-Poetic image-Rose sandal; الديوان – الصورة الشعرية – ردة نعل